The Effects of CACNA1C Gene Polymorphism on Spatial Working Memory in Both Healthy Controls and Patients with Schizophrenia or Bipolar Disorder - Zhang, Qiumei; Shen, Qiuge; Xu, Zhansheng; Chen, Min; Cheng, Lina; Zhai, Jinguo; Gu, Huang; Bao, Xin; Chen, Xiongying; Wang, Keqin; Deng, Xiaoxiang; Ji, Feng; et al. (Neuropsychopharmacology (New York, N.Y.), 2012)
CACNA1C gene polymorphism (rs1006737) is a susceptibility factor for both schizophrenia (SCZ) and bipolar disorder (BP). However, its role in working memory, a cognitive function that is impaired in both diseases, is not clear. Using three samples, including healthy controls, patients with SCZ, and patients currently in manic episodes of BP, this study tested the association between the SNP rs1006737 and spatial working memory as measured by an N-back task and a dot pattern expectancy (DPX) task. Among SCZ patients and healthy controls, the clinical risk allele was associated with impaired working memory, but the association was either in opposite direction or non-significant in patients with BP. These results indicated that rs1006737 may have differential effects on working memory in different disease populations and pointed to the necessity for more studies in different patient populations.